2022
DOI: 10.3390/su141912855
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance Assessment of Geothermal Asphalt Pavements: A Comparative Experimental Study

Abstract: This paper introduces shallow geothermal systems as a potential solution for improving the thermo-mechanical performance of asphalt under extreme climate events. With the recent changes experienced in the climate, earlier infrastructure failure can be expected, predominantly for temperature-sensitive flexible pavements. With that in mind, the efficiency of geothermal systems in terms of heating and cooling was comprehensively argued in many studies. However, very limited studies discussed the structural perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This substantial change in the viscosity of the asphalt mixture is usually the main reason behind the induced rutting and compressibility of the asphalt structure in high-temperature environments. On the other hand, the binder behaves as a fragile solid at low temperatures, while at medium temperatures, it exhibits more viscoelastic behavior (Al-Atroush et al., 2022 [ 27 ]). Although the asphalt mixture’s strength will rise, in this case, but the thermal stress will rise too, which usually surpasses the material strength causing thermal cracking.…”
Section: Climate Effects On the Flexible Pavementmentioning
confidence: 99%
“…This substantial change in the viscosity of the asphalt mixture is usually the main reason behind the induced rutting and compressibility of the asphalt structure in high-temperature environments. On the other hand, the binder behaves as a fragile solid at low temperatures, while at medium temperatures, it exhibits more viscoelastic behavior (Al-Atroush et al., 2022 [ 27 ]). Although the asphalt mixture’s strength will rise, in this case, but the thermal stress will rise too, which usually surpasses the material strength causing thermal cracking.…”
Section: Climate Effects On the Flexible Pavementmentioning
confidence: 99%
“…The inappropriate selection of paving materials, typically prescribed under the assumption of a stationary climate rather than considering the potential effects of climate change, was reported as the main reason for this increase. Considering the temperature sensitivity of the flexible pavement, several failures and distresses could be predicted [8][9][10]. Gudipudi et al, 2017 [11] have demonstrated that the anticipated rise in temperature during summertime heatwaves could significantly shorten the pavement life from 16 to 4 years and raise the maintenance costs by 100%.…”
Section: Introductionmentioning
confidence: 99%